Simulating a Rotational Inverted Pendulum Model by using Matlab and Easy Java Simulations - Oscar O. Rodríguez-Díaz; Edwin L. Téllez-Valderrama; Diego A. Gutiérrez-Ramírez (TecnoLógicas, 2012)
This paper presents the analysis, design and construction of a virtual simulator, in which the behavior of a non-lineal system as the rotational inverted pendulum is represented graphically in an interface. This uses an Applet of Java that allows users change parameters of the model. The use of this tool is a good alternative for bridging the gap between the theoretical concepts and the actual behaviors of a process. The server uses Matlab/Simulink as a calculation engine, taking advantage of its ease for constructing non-lineal models by using block diagrams. The user interface has been created by a free software tool called Easy Java Simulations that allows designing interactive graphical applications as 3D interfaces. Easy Java results an interesting tool for automatic control system education.